Intercultural Communication A Practical Guide - Novinger, Tracy (University of Texas Press, 2021)
Successfully communicating with people from another culture requires learning more than just their language. While fumbling a word or phrase may cause embarrassment, breaking the unspoken cultural rules that govern personal interactions can spell disaster for businesspeople, travelers, and indeed anyone who communicates across cultural boundaries. To help you avoid such damaging gaffes, Tracy Novinger has compiled this authoritative, practical guide for deciphering and following "the rules" that govern cultures, demonstrating how these rules apply to the communication issues that exist between the United States and Mexico. Novinger begins by explaining how a major proportion of communication within a culture occurs nonverbally through behavior and manners, shared attitudes, common expectations, and so on. Then, using real-life examples and anecdotes, she pinpoints the commonly occurring obstacles to communication that can arise when cultures differ in their communication techniques. She shows how these obstacles come into play in contacts between the U.S. and Mexico and demonstrates that mastering the unspoken rules of Mexican culture is a key to cementing business and social relationships. Novinger concludes with nine effective, reliable principles for successfully communicating across cultures